Four principles for glyph construction: stability, obstruction, density and demarcation - da Silva, Sérgio Luciano; Silva, Sérgio Antônio (InfoDesign, 2010)
The purpose of this paper is to present some particularities of the human sight perception as well as possible glyph construction strategies that can get rid of unwanted optical effects in typeface design. This analysis is based mainly on the studies developed by Peter Karow and Karen Cheng about optical illusion applied to typography and on the interpretation Walter Tracy and Victor Gaultney offer for the concepts of legibility and readability. From there on, the presentation of some known optical phenomena, in text and illustrations, is used as the basis for what we consider as the contribution of the present work to typeface design: the elaboration of four principles (stability, obstruction, density, and demarcation) and the organization of concepts, both aiming at proposing correction criteria and adjustments in the form of the glyphs. [ Download ]